Efectividad de tres bioestimulantes en el crecimiento, rendimiento y rentabilidad del maíz (Zea mays L.) - Solórzano Solórzano, Darío Javier (2025)
Biostimulation is a widely recommended technology to promote better growth rates, increase yields, and improve crop profitability. In this context, the objective of this research was to evaluate the effectiveness of three biostimulants on the growth, yield, and profitability of yellow maize (Zea mays) in Calceta, Manabí. The treatments evaluated were: fertilization + Stimplex (T1), fertilization + Fertistim (T2), fertilization + Abvidiol (T3), fertilization alone (T4), and a control treatment (T5). A randomized complete block design (RCBD) was used, with five treatments, four replicates, and a total of 20 experimental units. The main variables studied were root dry mass, leaf area, grain yield, and economic profitability. Data were analyzed using analysis of variance (ANOVA), and mean separation was performed using Tukey’s test at a 5% probability level. Leaf area, root dry mass, and grain yield were significantly affected (p < 0.05) by the evaluated treatments, with the biostimulation treatments outperforming both conventional fertilization and the control. The Stimplex biostimulant resulted in the highest yield of 10.39 t ha⁻¹ and the greatest economic return, with $0.75 earned for every dollar invested. However, all biostimulation treatments increased yield by more than 18% and achieved an economic gain greater than 60% compared to the conventional fertilization treatment without biostimulation. The use of biostimulants is agronomically beneficial and economically viable for enhancing the productivity and profitability of yellow maize.